Insulin glargine versus insulin degludec in patients failing on oral therapy in type 2 diabetes: A retrospective real world comparative data from India. Issue 3 (July 2016) - Ghosal, Samit; Sinha, Binayak; Gangopadhyay, Kalyan Kumar
Abstract: Objective: To compare the changes in various glycemic parameters in insulin-naïve type 2 diabetes mellitus (DM) patients who were initiated on insulin glargine or insulin degludec in a real world setting. Methods: Retrospective data were analyzed in consecutive type 2 DM patients in a real world setting, who failed oral therapy (at least 2 oral anti-diabetic drugs) and were initiated with either insulin glargine or insulin degludec. The parameters assessed were the changes in HbA1c, fasting plasma glucose, body weight, dose of Insulin and the total number of patient reported hypoglycemic episodes up to 6 months after initiation. Result: At baseline, insulin glargine and insulin degludec groups were similar in terms of gender, age, weight, HbA1c and duration of diabetes. After 6 months follow up the change in HbA1c (−1.09 versus −1.45 P  = 0.124), change in FPG (−72.81 mg/dl [−4mmol/L] versus −75.88 mg/dl [−4.2 mmol/L] P  = 0.755), and the change in body weight (+1.65 versus +0.85 P  = 0.082) were similar in glargine and degludec groups, respectively. Patients in insulin degludec group experienced significantly lesser patient reported hypoglycemic episodes (12 versus 40) and required significantly lesser dose (25.68 Units versus 18.61 Units per day; P  = 0.002) compared to insulin glargine. 41% of the patients reached HbA1C target of ≤7% with insulin glargine compared to 69% with insulin degludec within the specified time period. Conclusion: Results from this real world analysis suggest that among type 2 DM patients who were initiated on insulin degludec as compared to insulin glargine may be associated with significantly lesser patient reported hypoglycemic episodes and lesser dose of insulin while achieving similar glycemic control. This study is however limited by the retrospective nature of the data collection.